CARBON CAPTURE AND STORAGE(CCS) RESEARCH COLLABORATION TRENDS USING NETWORK ANALYSIS OF SCI PAPERS - Cho, Ha Young; Park, Noeon; Cho, Gabi; Ho Byun, Young (European Scientific Journal, ESJ, 2015)
Climate change has become one of the most important global agenda, and nations worldwide are taking actions to resolve the issue and contribute to the new climate change regime. In the case of South Korea, the new goal of reducing greenhouse gas emission to 37% below BAU(Business-As- Usual) was set. As a means to achieve this goal, the Korean government is actively investing in highly effective greenhouse reduction technologies such as solar cell, fuel cell, bioenergy, secondary battery, power IT, and CCS(Carbon Capture and Storage). This paper investigates the overall trend of CCS research by examining international CCS research collaboration characteristics through network analysis of SCI papers; collaboration network of Korea is analyzed in further detail. Such analysis helps understand the status of international research in the field of CCS, especially that of Korea.